Development of a Long Jump Education Model through a Game Approach to Improve Basic Movement for Students with Disabilities Grahita in Inclusive Schools at SMP Negeri 28 Surabaya - Ifanuddin Muchtar; Dwi Cahyo Kartiko; Abdul Rachman Syam Tuasikal (Budapest International Research and Critics in Linguistics and Education (BirLE) Journal, 2020)
The implementation of physical education, sports and health learning on the long jump subject has problems because the motion education model used is still the same as for regular students. The difficulties have an impact on their activities which tend to be passive, so a module is needed that is in accordance with the abilities and characteristics of students with mental disabilities. The purpose of this research is to produce a long jump module product through a game approach to improve basic motion in students with mental disabilities. The method used in this research is research and development using the Research & Development (R & D) development model from Borg and Gall. To develop a long jump educational model for mental disabilities with the aim of improving the basic locomotor, non-locomotor, and manipulative motion patterns. Prior to the implementation stage, 2 (two) people who are competent in the field of learning physical education for children with special needs are validated. Field trials consist of trial I and trial II. Limited trials were conducted at SMPN 28 Surabaya. Then, the evaluation stage is carried out by discussing with related parties in each school after the trial / implementation.The results of the analysis of the development of the long jump motion education model in the form of a long jump learning module through the game approach were carried out very well, and were feasible in the learning process with the results of two material validation experts 77% while the design validation obtained a score of 85%. The improvement of the basic long jump movement pattern is well done.